Triphos derivatives and diphosphines as ligands in the ruthenium-catalysed alcohol amination with NH3. Issue 16 (16th February 2016) - Nakagawa, N.; Derrah, E. J.; Schelwies, M.; Rominger, F.; Trapp, O.; Schaub, T.
Abstract : The ruthenium-triphos and diphosphine-catalysed amination of alcohols with ammonia is reported. Abstract : The ruthenium-triphos and diphosphine-catalysed amination of alcohols with ammonia is reported. Various types of triphos derivatives with electron-donating functional group were synthesized and used as ligands in the Ru-catalysed alcohol amination with NH3 . The triphos derivatives are effective for the formation of primary amines. On the other hand, if hemilabile diphosphines as tridentate ligands are used, mixtures of secondary-along with primary amines are obtained. It was found that even simple diphosphines can be used as ligands for the selective formation of the secondary amines. The diphosphine system allows a new entry to the Ru-catalysed formation of secondary amines.